RISK ASSESSMENT AND CONTROL OF GREEN FINTECH BUSINESS OF CHINESE BANKS IN THE CONTEXT OF DIGITAL ECONOMY: RESEARCH EVIDENCE FROM CHINA (International Journal of Management (IJM), 2023)
With the rapid development of the digital economy, widespread use of green finance and financial technology has led to significant results in the digital transformation of banks, and the accompanying financial risks of banks cannot be ignored, which has now become a relatively hot academic topic for international research. This study innovatively draws on the quality function deployment theory in marketing, combines the G1-entropy value method in fuzzy mathematics for quantitative calculation, outputs the calculation results through a combination of qualitative and quantitative approaches, and deeply explores the risk assessment of green fintech business of Chinese banks in the era of digital economy. In our research, we study the risk impact of digital economy on green fintech business from the perspective of overall level, and more importantly, this study applies the theory and method to the risk assessment of green fintech business of banks, constructs the risk assessment index system of green fintech business of Chinese banks, calculates the importance of each index quantitatively, and gives the ranking results of each index in order to demonstrate the applicability of the method. In addition, we also rely on this study to achieve innovation and practical application at the theoretical level, which enriches the academic theoretical knowledge of financial risk assessment and expands the research literature in this field, and at the same time, provides reference for the Chinese government and financial regulators to formulate the control of banks' financial risk business, and also provides relevant ideas and methodological support for similar international academic cases.